Analisa Kinerja Kapasitor Bank Pada Apartemen Gandaria Heights Jakarta - Alif Anshar; Ujang Wiharja (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2023)
The occurrence of a voltage drop in the electrical panel load in the common area of ??the Gandaria Heights apartment monitored by the Building Automation System (BAS) is caused by an erratic change in power factor (cosphi). Because according to data taken from recording through the daily logsheet, a power factor of 0.75 is obtained. Eliminating power losses in 3 phase electrical installations with a total power of 300 KVA is to improve the Power Factor against voltage drop disturbances. By adding a capacitor to the common area electrical panel which is indicated to have the lowest power factor. Based on calculations using field data, the total KVAR before and after repairs is 124 KVAR. If the existing capacitor has a value of 50 KVAR, then 3 step capacitors can be installed with a total of 150 KVAR. Thus leaving a reactive power of 26 KVAR or equivalent to 17.3% of the total power of 150 KVAR